Proposing an integrative, dynamic and transdiagnostic model for addictions: dysregulation phenomena of the three main modes of the predostatic mind - Loreto, Bibiana Bolten Lucion; Sordi, Anne Orgler; de Castro, Melina Nogueira; Ornell, Felipe; Guarnieri, Eduardo Pegoraro; Roza, Thiago Henrique; Schuch, Jaqueline Bohrer; Cima, Marcos da Silveira; Pechansky, Flavio; Grevet, Eugênio Horácio; Grassi-Oliveira, Rodrigo; von Diemen, Lisia; et al. (Frontiers in Psychiatry, 2024)
Several theories have been proposed to explain the complex diagnostic aspects related to addiction disorders. Recent frameworks tend to focus on dimensional perspectives of symptoms rather than categorical systems, since substance use disorders are frequently comorbid with other psychiatric disorders. However, useful transdiagnostic models that could integrate clinical evaluation derived from neuroscientific theories are lacking. In the present manuscript, the authors propose a model based on a new paradigm, in an attempt to better explain this complex, multifaceted phenomenon. The new paradigm presupposes that emotions and behavior are a response to risk prediction. Individuals make choices and engage in actions to manage potential risks/rewards in order to seek or maintain homeostasis in their internal and external environments -a mechanism that the authors call predostatic (predictive mechanism with homeostatic purpose). The model considers Three Main Modes of the Predostatic Mind: 1) Alarm Mode, activated by high and/or imminent risk prediction; 2) Seek Mode, activated by long-term risk or reward prediction; and 3) Balance Mode, a self-regulating state of mind related to low risk prediction, a soothing system and a calm state. Addiction is seen as a chronic dysregulation of organism systems leading to internalizing or externalizing phenomena mainly related to the Seek and Alarm Modes, which are persistently activated by reward and risk prediction, respectively, thus hindering Balance. Addiction neuroscience research has shown that chronic drug use or engagement in addictive behaviors can lead to neuroadaptations in the brain reward circuitry, disrupting normal balance and the regulation of reward processes. This dysregulation can contribute to persistent drug-seeking/addictive behaviors despite negative consequences. This newly proposed dynamic and integrative model, named Dysregulation based on Externalizing and Internalizing Phenomena of the Three Main Modes of the Predostatic Mind (DREXI3), proposes six dysregulation dimensions with basic emotional and behavioral symptoms, such as neurophysiological alterations, impulsivity, compulsion, cognitive impairment/psychosis, mood, and anxiety/anger. In this paper, the authors explain the rationale behind DREXI3 and present some hypothetical clinical examples to better illustrate the use of the model in clinical practice. The development of this innovative model could possibly guide tailored treatment interventions in the addiction field.